Complement, a Therapeutic Target in Diabetic Kidney Disease - Budge, Kelly; Dellepiane, Sergio; Yu, Samuel Mon-Wei; Cravedi, Paolo (Frontiers in Medicine, 2021)
Currently available treatments of diabetic kidney disease (DKD) remain limited despite improved understanding of DKD pathophysiology. The complement system is a central part of innate immunity, but its dysregulated activation is detrimental and results in systemic diseases with overt inflammation. Growing evidence suggests complement activation in DKD. With existent drugs and clinical success of treating other kidney diseases, complement inhibition has emerged as a potential novel therapy to halt the progression of DKD. This article will review DKD, the complement system’s role in diabetic and non-diabetic disease, and the potential benefits of complement targeting therapies, especially for DKD patients.